2019
DOI: 10.1088/1367-2630/ab3f5f
|View full text |Cite
|
Sign up to set email alerts
|

Multiband effects in equations of motion of observables beyond the semiclassical approach

Abstract: The equations of motion (EOM) for the position and gauge invariant crystal momentum are considered for multiband wave packets of Bloch electrons. For a localized packet in a subset of bands well-separated from the rest of the band structure of the crystal, one can construct an effective electromagnetic Hamiltonian with respect to the center of the packet. We show that the EOM can be obtained via a projected operator procedure, which is derived from the adiabatic approximation within perturbation theory. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 32 publications
(101 reference statements)
0
10
0
Order By: Relevance
“…The justification for a well-localized packet in real space comes from the semiclassical approximation used in transport for which the wavelengths of external fields are much larger than the spread of the packet in real space. We further note that multiband packets that are well localized in reciprocal and real spaces, one deals with degenerate or nearly degenerate Bloch states comprising the packets [13,15].…”
Section: Basic Assumptionsmentioning
confidence: 99%
See 4 more Smart Citations
“…The justification for a well-localized packet in real space comes from the semiclassical approximation used in transport for which the wavelengths of external fields are much larger than the spread of the packet in real space. We further note that multiband packets that are well localized in reciprocal and real spaces, one deals with degenerate or nearly degenerate Bloch states comprising the packets [13,15].…”
Section: Basic Assumptionsmentioning
confidence: 99%
“…The anomalous velocity can give rise to a variety of Hall effects associated with charge carriers and photons as well as unusual thermoelectricity [7][8][9][10][11]. On the other hand, several researchers have considered Bloch electron wave packets extending over multiple energy bands [12][13][14][15][16]. In fact, it has been shown that the equations of motion for the centers of such multiband wave packets are different than those in the single band wave packet case, and one can obtain new features in the dynamics of spin, parity polarization currents, and non-Abelian transport [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations